Kurikulum Merdeka in early childhood Islamic education for character and spirituality - Mursal Aziz; Muhammad Hasbie Ashshiddiqi; Sri Nurmala Sari (Universitas Pendidikan Indonesia, 2025)
This study aims to examine the implementation of the Kurikulum Merdeka in early childhood Islamic education, with a particular focus on shaping character and spirituality from an early age. The background of this research is based on the need for an educational model that emphasizes not only cognitive aspects but also the development of strong moral and spiritual values during a child's formative years. The main issue raised is how the Kurikulum Merdeka can be effectively integrated with Islamic education to shape children's character and spirituality. This study employs a qualitative approach, utilizing a literature review method, to examine literature related to the Kurikulum Merdeka, early childhood Islamic education, and theories of character and spiritual formation. The results of the study indicate that the Kurikulum Merdeka provides significant scope for strengthening Islamic values through a contextual, differentiated, and student-centered learning approach. The integration of Islamic teachings with the Pancasila Student Profile can enhance children's character development, including honesty, empathy, responsibility, and spiritual awareness. This study concludes that the Kurikulum Merdeka can synergize effectively with Islamic education, becoming the right strategy for shaping a young generation that is not only academically intelligent but also has a strong foundation in character and spirituality. Abstrak Penelitian ini bertujuan untuk mengkaji implementasi Kurikulum Merdeka dalam pendidikan Islam anak usia dini, khususnya dalam membentuk karakter dan spiritualitas sejak dini. Latar belakang penelitian ini didasarkan pada kebutuhan akan model pendidikan yang tidak hanya menekankan aspek kognitif, tetapi juga pembentukan nilai-nilai moral dan spiritual yang kuat pada masa keemasan anak. Masalah utama yang diangkat adalah bagaimana Kurikulum Merdeka dapat berbaur secara efektif dengan pendidikan Islam agar mampu membentuk karakter dan spiritualitas anak. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka, yang mengkaji literatur terkait Kurikulum Merdeka, pendidikan Islam anak usia dini, serta teori pembentukan karakter dan spiritualitas. Hasil kajian menunjukkan bahwa Kurikulum Merdeka memberikan ruang besar bagi penguatan nilai-nilai keislaman melalui pendekatan pembelajaran yang kontekstual, diferensiatif, dan terpusat pada murid. Integrasi nilai-nilai ajaran Islam dengan Profil Pelajar Pancasila dapat memperkuat pembentukan karakter anak seperti kejujuran, empati, tanggung jawab, dan kesadaran spiritual. Simpulan dari penelitian ini adalah bahwa Kurikulum Merdeka dapat bersinergi secara efektif dengan pendidikan Islam, dan menjadi strategi yang tepat dalam membentuk generasi muda yang tidak hanya cerdas secara akademik, tetapi juga memiliki landasan karakter dan spiritualitas yang kuat. Kata Kunci: karakter; Kurikulum Merdeka; PAUD; pendidikan anak usia dini; spiritual